10 PENDAPAT AHLI MENGENAI KEUNGGULAN KOMPETITIF - Amelia Putri; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2025)
This article presents an in-depth analysis of ten expert opinions on competitive advantage, an essential concept in business strategy. Competitive advantage not only serves as a tool to differentiate a company from competitors, but also as a driver of innovation and sustainable growth. Through a qualitative approach, this research gathers views from experts in the fields of management and economics, highlighting key variables such as product differentiation, customer satisfaction, and adaptation to market changes. The findings show that companies that are able to integrate these various perspectives tend to be more successful in maintaining their market position. Thus, this article makes a significant contribution to the understanding of competitive advantage theory and its effectiveness in managerial practice, as well as offering strategic recommendations for business leaders in establishing policies that are responsive to industry dynamics.